2005
DOI: 10.1093/bioinformatics/bti356
|View full text |Cite
|
Sign up to set email alerts
|

WebAllergen: a web server for predicting allergenic proteins

Abstract: http://weballergen.bii.a-star.edu.sg/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The performance PSSM based SVM model was also compared to AlgPred [4] and WebAllergen [5,6] models (see Figure 1c). We submitted an independent dataset of 97 allergens and equal number of non allergens to these models.…”
Section: Discussionmentioning
confidence: 99%
“…The performance PSSM based SVM model was also compared to AlgPred [4] and WebAllergen [5,6] models (see Figure 1c). We submitted an independent dataset of 97 allergens and equal number of non allergens to these models.…”
Section: Discussionmentioning
confidence: 99%
“…According to the FAO/WHO method 7, AllergenPro provide the function to find the query protein for an 80 amino acids sliding window by a FASTA alignment program. Motif-based prediction method [6] provides the function to compare the two sequences with the specific profiles between the conserved motifs and the unique sequences. If specific protein is predicted to be allergenic, query result will be displayed to compare against a set of well-known allergenic motifs.…”
Section: Methodsmentioning
confidence: 99%
“…This method employs MEME motifs of a length of 50 residues for the prediction of allergenicity by using pairwise sequence alignment with certain threshold. WebAllergen [72] is a web server for the prediction of allergenic proteins which is also based on specific detectable allergenic motifs in known allergens [73]. Furthermore, a study carried out by Kong et al showed that an approach based on search of multiple motifs is more specific and efficient than the conventional single motif search [74].…”
Section: Motif-based Approachesmentioning
confidence: 99%